Supply Chain Risk Management Analysis Using the House of Risk (HOR) and Analytical Network Process (ANP) at PT XYZ - Putri Dwi Raudhatul Jannaah; Dira Ernawati; Isna Nugraha (LPPM Institut Pendidikan Nusantara Global, 2026)
The supply chain in the quartz sand mining and processing industry is characterized by a high level of uncertainty, which can potentially cause risks that disrupt operational performance. PT XYZ faces various supply chain risks across planning, mining, processing, and distribution activities, resulting in gaps between planned and actual production. The study focuses on evaluating risks within the supply chain and determining which mitigation measures should take priority. An integrated approach was applied, combining the SCOR model, the two phases of the House of Risk (HOR), and the Analytical Network Process (ANP) guided by the BOCR criteria. Data collection involved field observations, interviews, Focus Group Discussions (FGDs), and surveys. Out of 23 identified risk events and 23 associated agents, 14 were highlighted as the most critical based on the 80/20 Pareto rule, forming the foundation for targeted mitigation efforts. Further evaluation through HOR phase 2 resulted in 14 mitigation strategies, with strategy PA9 achieving the highest Effectiveness to Difficulty Ratio (ETDk) score of 3582. Furthermore, the ANP results indicate that Alternative 1 (PA9) has the highest priority weight of 0.12623, followed by Alternative 2 (PA3) with a weight of 0.11040 and Alternative 3 (PA1) with a weight of 0.10401. These three alternatives are therefore identified as the priority mitigation strategies for PT XYZ.